Diversity‐Oriented Metal‐Free Synthesis of Nitrogen‐Containing Heterocycles Using Atropaldehyde Acetals as a Dual C3/C2‐Synthon. Issue 20 (13th September 2022) - Chen, Shaomin; You, Bo; Zhang, Tianjian; Li, Minghao; Gu, Yanlong
Abstract: A highly efficient and elegant diversity‐oriented reaction paradigm employing atropaldehyde acetals as new dual C2/C3 synthons was developed under metal‐free conditions using glycine esters as the counterpart reagents, which allowed rapid synthesis of two important nitrogen‐containing heterocycles, pyrrolo[1, 2‐ a ]quinolines and 3, 5‐diarylpyridines. The divergent products are subtly controlled by the manipulation of the substitutional groups of glycine esters. When a N ‐arylglycine ester was used, pyrrolo[1, 2‐ a ]quinolines can be formed through cascade oxidative C−C cleavage/multiple cyclization. Instead, N ‐benzylglycine ester as the counter‐reagent led to the synthesis of 3, 5‐diarylpyridines via two key C−N cleavages. Mild conditions, broad substrate scope, scalability and environmentally acceptable organic solvents rendered this method practical and attractive. Abstract : Diverse as one can : Atropaldehyde acetals can serve as dual C3/C2‐synthons to react selectively with glycine esters in industrially acceptable solvents, that is, diethyl carbonate or acetonitrile, with the aid of trifluoroacetic acid. On the basis of these reactions, diversity‐oriented synthesis of nitrogen‐containing heterocycles, pyrrolo[1, 2‐ a ]quinolines and 3, 5‐diarylpyridines, is successfully established.